Studi Pengaruh Variasi Resin terhadap Laju Korosi pada Material FRP - Novitrie, Nora Amelia; Alvido Toto Wijaya; Bambang Antoko (2477 - 6165, 2020)
Pipes in the oil and gas industry use carbon steel which contains a corrosive fluid with fluctuating acidity. This condition causes the corrosion resistance of the pipe to decrease so that other materials that are more resistant to corrosive conditions are needed, for example Fiberglass Reinforced Plastic (FRP). FRP is a composite material made of resin which is then formed into pipes. In this study, trials were carried out on polyester resin, silicon rubber resin and epoxy resin to determine the value of their corrosion rate. The level of resistance of a material to corrosion generally has a corrosion rate value between 0.025 - 5.08 mmpy. The method used is the immersion test of the specimen using the ASTM G31 - 72 standard.The results obtained from this experiment are that polyester has the lowest corrosion rate than epoxy and silicon rubber and polyester resin with a fiber composition of 40% and fiber position 40° has a corrosion rate of 0.566 mmpy so that it meets the level of resistance of a material to corrosion.